Life Without Parole, America's Other Death Penalty: Notes on Life Under Sentence of Death by Incarceration - Johnson, Robert; McGunigall-Smith, Sandra (The Prison Journal, 2008)
Life without parole is examined as a form of death penalty, namely, death by incarceration as distinct from death by execution. Original interviews with a sample of prisoners (condemned prisoners and life-without-parole prisoners) and prison officers are used to develop a picture of the experience of life under sentence of death by incarceration. It is argued that offenders sentenced to death by incarceration do not pose a special danger to others in the prison world or in the free world and that the suffering they experience is comparable to the suffering endured by condemned prisoners. Life without parole thus emerges as a viable alternative to the capital punishment.